SHM_415447_HST_3D Pressure-Flaked Fint Dagger (Broken) - Qallaki, Ylber; National Historical Museums (National Historical Museums, 2026)
Photogrammetric model of a broken pressure-flaked flint dagger (type IV) from the Swedish Late Neolithic. Collected from Svasstorp in Ljungby parish, Halland, Sweden in 1888, it is now held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=1005

Link to Sök I Samlingarna

https://samlingar.shm.se/object/076ADF16-B78B-4D4B-AD54-2701C359E99E
Keywords: Archaeology; Archaeology; Archaeology/history; Swedish Neolithic; Dynamic Collections; Museum Object; 3D Model; Photogrammetry; Svasstorp; History and archaeology; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi